Meningkatkan Minat Berwirausaha Mahasiswa Melalui Jiwa Kewirausahaan, Pendidikan Kewirausahaan, Lingkungan Keluarga dan Ide Bisnis - Aisyah Nurul Sakinah; Hardi Utomo; Budi Riyanti (Jurnal Ilmiah Wahana Pendidikan, 2026)
In fact, the largest contributors to unemployment in Indonesia come from high school and college graduates. This fact is in contrast to the common belief that the higher a person's education, the greater their opportunities in finding work. Almost all college graduates focus on being job seekers rather than job creators. In reality, the opportunity to become an entrepreneur in Indonesia is still quite large. However, only a handful of college graduates choose to enter the world of entrepreneurship. This is due to several factors such as fear of failure, a lack of understanding of entrepreneurship, lack of support from those around them, being looked down upon, and lack of capital to start a business. The purpose of this study was to determine the influence of entrepreneurial spirit, entrepreneurship education, family environment, and business ideas on entrepreneurial interest among students of STIE AMA Salatiga. A sample of 118 students was taken using a purposive sampling technique. The analytical methods used were validity test analysis, reliability test, and multiple linear regression tests (t-test, f-test, and coefficient of determination). The results showed that the variables of entrepreneurial spirit, entrepreneurship education, and family environment have a significant influence on entrepreneurial interest among students of STIE AMA Salatiga. A sample of 118 students was taken using a purposive sampling technique. The analytical methods used were validity test analysis, reliability test, and multiple linear regression tests (t-test, f-test, and coefficient of determination). The results showed that the variables of entrepreneurial spirit, entrepreneurship education, and family environment have a significant influence on entrepreneurial interest. However, the business idea variable does not have a significant influence on entrepreneurial interest.